Answer:
Please check the explanation.
Step-by-step explanation:
We know that:
A function is even if f(-x)=f(x) for all x ∈ R
A function is odd if f(-x)=-f(x) for all x ∈ R
1)
f(x)=x-x
f(-x)=-x-(-x)=-x+x=0
Parity of 0: Even and odd
2)
f(x) = x² – 3x + 2
f(-x)=(-x)²-3(-x)+2
= x²+3x+2
As
f(-x) ≠ f(x) and also f(-x) ≠ -f(x)
So, f(x) = x² – 3x + 2 is neither od nor even
3)
f(x)=(x-2)
f(-x)=(-x-2)
f(-x) ≠ f(x) and also f(-x) ≠ -f(x)
So, f(x)=(x-2) is neither odd nor even
4)
f(x) = 1x¹
f(-x)=1(-x)¹
=-x
As
f(-x)=-f(x)
Thus, f(x) = 1x¹ is odd function.